Development and Validation of a Nomogram Based on Red Blood Cell and Reticulocyte Parameters for Differentiating Thalassemia Trait From Iron Deficiency Anemia - Yong Chen; Yazhen Mao; Jie Liu; Yice Lin; Dandan Chen (Journal of Clinical Laboratory Analysis, 2026)
ABSTRACT Introduction Thalassemia trait (TT) and iron deficiency anemia (IDA) are the most common causes of microcytic hypochromic anemia with overlapping hematological features, complicating differential diagnosis. This study developed and internally validated a nomogram incorporating red blood cell (RBC) and reticulocyte parameters to preliminarily distinguish TT from IDA. Methods A retrospective cohort of 517 patients (320 IDA, 197 TT) was randomly divided into training ( n = 361) and validation ( n = 156) cohorts at a 7:3 ratio using stratified random sampling according to diagnostic group. RBC parameters (RBC count, MCV, MCH) and reticulocyte indices (RET%, IRF, LFR, MFR, HFR) were collected. LASSO regression identified key variables, followed by multivariate logistic regression. Model performance was evaluated using ROC curves, calibration plots, and decision curve analysis (DCA). Results LASSO regression selected four predictors: RBC count, MCV, RET%, and HFR. Multivariate analysis showed elevated MCV ( p < 0.001), RET% ( p < 0.001), and HFR ( p < 0.001) were associated with IDA, while elevated RBC count ( p < 0.001) predicted TT. The nomogram achieved excellent discrimination with AUC of 0.900 in training and 0.904 in validation cohorts. Calibration plots showed good agreement and DCA suggested potential clinical net benefit across threshold probabilities of 7%–96% (training) and 5%–97% (validation). Conclusions This nomogram integrating RBC count, MCV, RET%, and HFR showed promising performance for the preliminary differentiation of TT from IDA and may serve as a practical, noninvasive screening aid for risk stratification and prioritization of confirmatory testing. It should not be used as a substitute for hemoglobin electrophoresis, thalassemia genetic testing, or iron studies.